Development of Low‐Gain Avalanche Detectors in the Frame of the Acceptor Removal Phenomenon. Issue 17 (19th June 2022) - Lauer, Kevin; Peh, Katharina; Krischok, Stefan; Reiß, Stephanie; Hiller, Erik; Ortlepp, Thomas
Abstract : Low‐gain avalanche detectors (LGAD) suffer from an acceptor removal phenomenon due to irradiation. This acceptor removal phenomenon is investigated in boron, gallium, and indium implanted samples by 4‐point‐probe (4pp) measurements, low‐temperature photoluminescence spectroscopy (LTPL), and secondary ion mass spectrometry (SIMS) before and after irradiation with electrons and protons. Different co‐implantation species are evaluated with respect to their ability to reduce the acceptor removal phenomenon. In case of boron, the beneficial effect is found to be most pronounced for the low‐dose fluorine and high‐dose nitrogen co‐implantation. In case of gallium, the low‐dose implantations of carbon and oxygen are found to be beneficial. For indium, the different co‐implantation species have no beneficial effect. SIMS boron concentration depth profiles measured before and after irradiation show no indication of a fast movement of boron at room temperature. Hence, the discussed BSi –Sii ‐defect explanation approach of the acceptor removal phenomenon seems to be more likely than the other discussed Bi –Oi ‐defect explanation approach. Abstract : Low gain avalanche detectors (LGAD) suffer from acceptor removal after irradiation. This is investigated in boron, gallium and indium implanted silicon by three methods. Secondary ion mass spectrometry (SIMS) boron depth profiles measured before and after irradiation show no fast movement of boron at room temperature. Hence, explanation by the BSi –Sii ‐defect seems to be more likely than by the Bi –Oi ‐defect.